Cytokine amplification and macrophage effector functions in aortic inflammation and abdominal aortic aneurysm formation - Ijaz, Talha; Tilton, Ronald G.; Brasier, Allan R. (Journal of Thoracic Disease; Vol 8, No 8 (August 01, 2016): Journal of Thoracic Disease, 2016)
On April 29, 2015, Son and colleagues published an article entitled “Granulocyte macrophage colony-stimulating factor (GM-CSF) is required for aortic dissection/intramural haematoma” in Nature Communications. The authors observed that the heterozygous Kruppel-like transcription factor 6 (KLF6) deficiency or absence of myeloid-specific KLF6 led to upregulation of macrophage GM-CSF expression, promoted the development of aortic hematoma/dissection, and stimulated abdominal aortic aneurysm (AAA) formation when the vessel wall was subjected to an inflammatory stimulus. The additional findings of increased adventitial fibrotic deposition, marked infiltration of macrophages, and increased expression of matrix metalloprotease-9 (MMP-9) and IL-6 were blocked with neutralizing GM-CSF antibodies, or recapitulated in normal mice with excess GM-CSF administration. The authors concluded that GM-CSF is a key regulatory molecule in the development of AAA and further suggested that activation of GM-CSF is independent of the transforming growth factor β (TGFβ)-Smad pathway associated with the Marfan aortic pathology. In this perspective, we expand on this mechanism, drawing from previous studies implicating a similar essential role for IL-6 signaling in macrophage activation, Th17 expansion and aortic dissections. We propose a sequential “two-hit” model of vascular inflammation involving initial vascular injury followed by recruitment of Ly6Chi macrophages. Aided by fibroblast interactions inflammatory macrophages produce amplification of IL-6 and GM-CSF expression that converge on a common, pathogenic Janus kinase (JAK)-signal transducers and activations of transcription 3 (STAT3) signaling pathway. This pathway stimulates effector functions of macrophages, promotes differentiation of Th17 lymphocytes and enhances matrix metalloproteinase expression, ultimately resulting in deterioration of vascular wall structural integrity. Further research evaluating the impact of interventions modulating this common JAK-STAT3 pathway may yield new therapeutic interventions for late stages of vascular expansion in inflammation driven aortic disease.